A cross-sectional study of functional disabilities and perceived cognitive dysfunction in patients with major depressive disorder in South Korea: The PERFORM-K study. (30th May 2016) - Kim, Jae Min; Chalem, Ylana; di Nicola, Sylvia; Hong, Jin Pyo; Won, Seung Hee; Milea, Dominique
Abstract: PERFORM-K was a cross-sectional observational study that investigated functional disability, productivity and quality of life in MDD outpatients in South Korea, and the associations of these with depressive symptoms, perceived cognitive dysfunction and other factors. A total of 312 outpatients who started antidepressant monotherapy underwent a single study interview. Physicians and patients assessed depression severity. Patients also assessed: perceived cognitive dysfunction, functional disability, impaired productivity and quality of life. Patients had moderate to severe depression (MADRS mean total score: 28.9±7.3), and reported marked functional disability (SDS mean total score: 16.7±8.6), impaired productivity (WPAI mean overall work productivity loss: 52.4±31.8%), perceived cognitive dysfunction (PDQ-D mean total score: 29.9±18.6) and impaired quality of life (EQ-5D mean utility index score of 0.726±0.192). Greater functional disability and impairment in daily activities were associated with more severe depression and greater perceived cognitive dysfunction. Irrespective of depression severity, patients with more severe perceived cognitive dysfunction reported worse work-related productivity outcomes (higher presenteeism and greater overall work productivity loss). PERFORM-K confirms the impact of MDD on functional status and well-being in South Korean patients, and highlights the importance of recognising cognitive dysfunction in clinical practice. Highlights: 312 patients in South Korea initiating antidepressant monotherapy were interviewed. Patients had moderate/severe depression and marked functional disability. Depression affected patients' functioning, productivity and quality of life (QoL). Perceived cognitive dysfunction also affected functioning, productivity and QoL. Cognitive dysfunction affected productivity irrespective of depression severity.